Assessing the Effects of Repetitive Transcranial Magnetic Stimulation on Cognition in Major Depressive Disorder Using Computerized Cognitive Testing. Issue 3 (September 2016) - Galletly, Cherrie; Gill, Shane; Rigby, Ashlee; Carnell, Benjamin Luke; Clarke, Patrick
Abstract : Objectives: A range of different treatment approaches are available for depression; however, there is an ongoing concern about the cognitive impairment associated with many treatments. This study investigated the effect of treatment with repetitive transcranial magnetic stimulation (rTMS) on cognition in patients with major depressive disorder. Cognition before and after treatment was assessed using a computerized cognitive testing battery, which provided comprehensive assessment across a range of cognitive domains. This was a naturalistic study involving patients attending an outpatient clinical rTMS service. Methods: A total of 63 patients with treatment-resistant depression completed the IntegNeuro cognitive test battery, a well-validated comprehensive computerized assessment tool before and after receiving 18 or 20 treatments of sequential bilateral rTMS. Change in the various cognitive domains was assessed, and analyses were undertaken to determine whether any change in cognition was associated with a change in rating of depression severity. Results: There was a significant decrease in Hamilton Depression Rating Scale scores from baseline to posttreatment. There was no decline in performance on any of the cognitive tests. There were significant improvements in maze completion time and the number of errors in the maze task. However, these were accounted for by improvement in mood when change in depressive symptoms was included as a covariate. Conclusions: This open-label study provides further support for the efficacy and safety of rTMS as a treatment option for people with major depressive disorder in a naturalistic clinical setting. Using a comprehensive, robust computerized battery of cognitive tests, the current study indicated that there was no significant cognitive impairment associated with rTMS and that any improvements in cognitive functioning were associated with a reduction in depressive symptoms.